Describing and comparing the availability of acute care resources to treat new onset stroke in different income settings : a self-reported survey of acute care providers at the 2016 international conference on emergency medicine - Chunga, Ramadhan Mohamed (Stellenbosch : Stellenbosch University, 2019)
Thesis (MMed)--Stellenbosch University, 2019.